Mentha cervina communities in Portugal - Silva, Vasco; Póvoa, Orlanda; Espírito-Santo, Maria Dalila; Vasconcelos, Teresa; Monteiro, Ana (Lazaroa, 2010)
Mentha cervina is traditionally used in the Alentejo region as a seasoning for fish dishes, as well as for medicinal purposes. The species has been disappearing in the wild, due mainly to excessive collection, overgrazing, and habitat destruction. Fifteen M. cervina locations situated in mainland Portugal and Spain (Extremadura) were studied using the phytosociological approach. M. cervina is characteristic of the Menthion cervinae alliance – tall therophyte plant communities with a long flooding period that lasts until summer. All the relevés correspond to the Cypero badii-Menthetum cervinae association.